Phytochemical Characterization of Phenolic Compounds by LC-MS/MS and Biological Activities of Ajuga reptans L., Ajuga salicifolia (L.) Schreber and Ajuga genevensis L. from Turkey - Goger, Gamze; Kose, Yavuz Bulent; Demirci, Fatih; Goger, Fatih (Galenos Publ House, 2021)
Objectives: In this study, it was aimed to characterize the phenolic contents of Ajuga reptans L., Ajuga salicifolia (L.) Schreber and Ajuga genevensis L. and to investigate their in vitro antioxidant and antimicrobial activities. Materials and Methods: Air dried aerial parts of A. reptans L., A. salicifolia (L.) Schreber, and A. genevensis L. collected from Turkey were extracted with methanol (70%), and the phenolic composition of the crude extracts was analyzed by liquid chromatography with tandem mass spectrometry (LC-MS/MS) method. To determine the total phenolic content the Folin-Ciocalteu method was used. The radical scavenging activities of the extracts were evaluated by the photometric 1,1-diphenyl-2-picrylhydrazyl radical, and trolox equivalent antioxidant capacity assays (TEAC). Furthermore, Ajuga sp. extracts were tested against Escherichia coli NRRL B3008, Staphylococcus areus ATCC 6538, Salmonella thyphimurium ATCC 13311, Bacillus cereus NRRL B-3711, Candida albicans ATCC 90028, Candida tropicalis ATCC 1369, and Candida parapsilosis ATCC 22019 using the in vitro broth dilution assay. Results: The LC-MS/MS analyses identified 19 compounds. The amount of total phenolics ranged from 30.0 to 42.2 mg gallic acid equivalent/g in all extracts. According to the results of TEAC assay, the tested extracts were found to have relatively high activity at 1.2-1.5 mM concentrations. Ajuga sp. extracts inhibited all tested microorganisms; however, C. albicans, C. tropicalis, and C. parapsilosis exhibited relatively more susceptibility (minimum inhibitory concentration: 156.25 mu g/mL) compared to the bacteria tested. Conclusion: The antioxidant activities of all extracts were determined for the first time by the TEAK method, and the in vitro antimicrobial activity of A. salicifolia was investigated for the first time against selected strains.
Keywords: Ajuga reptans; Ajuga salicifolia; Ajuga genevensis; LC-MS/MS; antioxidant activity; antimicrobial activity